Indian women and public space: women’s landscape of Fordsburg, Johannesburg - Mohamed, Sumayya (My University, 2017)
The urban spatial restrictions women are subjected to are universally acknowledged. These restrictions, which exist physically and symbolically within space, are used as a tool for gendered ‘othering’ and exclusion. Using a conceptual framework that include structures of power, spatial and gender theories as a tool of analysis this research seeks to analyse and track the process of spatial restrictions on the female body in their everyday lived experiences. The socio-political undercurrents of urban space is entangled within the power structures and ideologies that govern and objectify women’s presence and behaviours within public space. This has a debilitating effect on the way they access and use it. Indian women in Fordsburg are no strangers to these universal problems. They experience many of the same fears that have been documented within the Public sphere. Their resilience and constant presence in public space questions the validity of the Public/Private binary as well as common stereotypical assumptions surrounding their identities which operate at different scales. Their everyday lived experience showcases their strategies in coping and overcoming the challenges the complex nature of urban public space presents to them. Their strategies of reclaiming the space are unique and intricate. Their resilience in challenging the normalization of socio-spatial dynamics leads them towards reclaiming their identities, power and respect as women.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science, 2017
Keywords: Urbanization; Public spaces; Cities and towns; Architecture and women